Analisis Hambatan Pelaksanaan Asesmen Terpadu dalam Menentukan Rehabilitasi atau Pemidanaan Bagi Pengguna Narkotika: Studi Kasus di BNN Kota Surabaya - Nagasha Suzena, Ryan Nata; Nurwahyuni, Mega Tita; Agustian Namara Putra, Farel; Aliya Dwi Nur Azizah , Ismil (CV. Era Digital Nusantara, 2025)
This study aims to analyze the obstacles in implementing the integrated assessment process as a basis for determining rehabilitation or criminal prosecution for drug users, with a case study at the Surabaya City National Narcotics Agency (BNN). The integrated assessment serves as a crucial mechanism to distinguish drug abusers eligible for rehabilitation from those who should face legal prosecution. However, in practice, its implementation encounters several challenges, including procedural delays, limited human resources, and lack of coordination among law enforcement institutions. Using a juridical-empirical approach and descriptive qualitative methods, the study reveals that these barriers affect the quality of assessments, lead to inaccurate recommendations, and increase the risk of over-criminalization. The study recommends cross-sectoral training, enhanced inter-agency coordination, and improved assessor capacity to ensure the integrated assessment is conducted effectively, fairly, and in line with restorative justice principles and the recovery-oriented approach for drug users.